Adolescent Identity Formation Under Terminal Illness: A Psychosocial Education Approach - Lathifah, Hasna; Prastiwi, Yeny (CV. INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: The primary purpose of this research is to investigate the struggle of forming adolescent identity through terminal illness as depicted in the film Clouds (2020), directed by Justin Baldoni. The study analyzes the real-life story of Zach Sobiech, who was diagnosed with osteosarcoma, through the lens of Erikson's psychosocial theory, specifically focusing on the stage of identity versus role confusion. Materials and methods: This study employs a qualitative descriptive approach using content analysis methodology. Primary data was collected from the film Clouds (2020) through systematic viewing and dialogue analysis. Secondary data included scholarly articles, theses, and relevant literature discussing the film and psychosocial development theory. Data analysis focused on identifying elements related to Erikson's identity versus role confusion stage, examining how Zach's limited life expectancy influenced his identity formation process. Results: The analysis reveals that terminal illness significantly accelerates the adolescent identity formation process. Despite facing osteosarcoma, Zach Sobiech demonstrated remarkable resilience in pursuing his dreams of becoming a singer, maintaining relationships, and creating meaningful experiences. The study identifies three key themes: the intensification of identity exploration under time constraints, the role of creative expression in identity formation, and the impact of terminal illness on developmental priorities and life meaning. Conclusions: Terminal illness does not necessarily impede adolescent identity formation but rather transforms and accelerates the process. The research demonstrates that when faced with mortality, adolescents may develop a more focused and purposeful approach to identity development, prioritizing authentic self-expression and meaningful relationships. This study contributes to understanding how extreme life circumstances can influence psychosocial development and provides insights for educators and healthcare professionals working with terminally ill adolescents.